Host life-history traits predict haemosporidian parasite prevalence in tanagers (Aves: Thraupidae). Issue 1 (13th January 2023) - Aguiar de Souza Penha, Victor; Maia Chaves Bicalho Domingos, Fabricius; Fecchio, Alan; Bell, Jeffrey A.; Weckstein, Jason D.; Ricklefs, Robert E.; Braga, Erika Martins; de Abreu Moreira, Patrícia; Soares, Letícia; Latta, Steven; Tolesano-Pascoli, Graziela; Alquezar, Renata Duarte; et al.
Abstract: Abstract: Vector-borne parasites are important ecological drivers influencing life-history evolution in birds by increasing host mortality or susceptibility to new diseases. Therefore, understanding why vulnerability to infection varies within a host clade is a crucial task for conservation biology and for understanding macroecological life-history patterns. Here, we studied the relationship of avian life-history traits and climate on the prevalence of Plasmodium and Parahaemoproteus parasites. We sampled 3569 individual birds belonging to 53 species of the family Thraupidae. Individuals were captured from 2007 to 2018 at 92 locations. We created 2 phylogenetic generalized least-squares models with Plasmodium and Parahaemoproteus prevalence as our response variables, and with the following predictor variables: climate PC1, climate PC2, body size, mixed-species flock participation, incubation period, migration, nest height, foraging height, forest cover, and diet. We found that Parahaemoproteus and Plasmodium prevalence was higher in species inhabiting open habitats. Tanager species with longer incubation periods had higher Parahaemoproteus prevalence as well, and we hypothesize that these longer incubation periods overlap with maximum vector abundances, resulting in a higher probability of infection among adult hosts during their incubation period and among chicks. Lastly, we found that Plasmodium prevalence was higher in species without migratory behaviour, with mixed-species flock participation, and with an omnivorous or animal-derived diet. We discuss the consequences of higher infection prevalence in relation to life-history traits in tanagers.